Major congenital malformations in offspring of women with chronic diseases-impact of the disease or the treatment? - Laila Ülkü Demir, BSc (Med); Elisabeth Reinhardt Mathiesen, DMSc; Peter Damm, DMSc; Lene Ringholm, PhD (Elsevier, 2023)
In a narrative review, we summarized previous findings on the risk of major congenital malformations in offspring of women with chronic hypertension, hypothyroidism, or depression compared with the background population, and evaluated whether exposure to medical treatment in the first trimester affected this risk. In a literature search in the PubMed database, cohort studies were included if they were published from 2010 to 2022 and contained data on major congenital malformations from ≥500 offspring of women with chronic hypertension, hypothyroidism, or depression during the first trimester of pregnancy, and data on both untreated and treated women. Data were compared with the background population of women without these diseases. In total, 7 cohort studies were identified. In comparison with the background population, 2 studies including 54,996 offspring of women with chronic hypertension showed an adjusted odds ratio of 1.20 to 1.30 for major congenital malformations in the offspring, regardless of antihypertensive treatment. One study including 16,364 offspring of women with hypothyroidism showed an adjusted odds ratio of 1.14 (1.06-1.22) for major congenital malformations in the offspring, regardless of thyroid substitution. Four studies including 48,913 offspring of women with depression showed adjusted odds ratios of 1.07 to 1.27 (0.91-1.78) for major congenital malformations in the offspring of untreated women. Three of these 4 studies showed similar prevalence of malformations in women treated for depression. The findings of this narrative review suggest that chronic hypertension and hypothyroidism, rather than exposure to their medical treatments in the first trimester, were associated with increased risk of major congenital malformations, whereas depression was generally not associated with major congenital malformations.